Multi-Facility Assessment of Variation in Transmission-Based Precautions (TBP) Policies and Healthcare Personnel (HCP) Personal Protective Equipment (PPE) Use Behavior. (4th October 2017) - Croft, Lindsay D; Drews, Frank; Berryrieser, Dennis; Haroldsen, Candace; Nevers, McKenna; Huber, Tavis; Donskey, Curtis; Krein, Sarah L; Safdar, Nasia; Fiore, Anthony E; Jernigan, John A; Slayton, Rachel B; et al.
Abstract: Background: The CDC provides guidelines for TBP but leaves specific policy decisions for PPE required for antibiotic-resistant organisms to individual facilities. This has potential to create variation in interfacility TBP policies. In a multi-facility study, we sought to (1) assess the level of variation in application of the CDC guideline and (2) determine if hospital-level policy intensity or complexity may be related to HCP PPE donning behavior. Methods: Observers at 6 acute care facilities received training on hand hygiene (HH) and PPE observations. Transmission-based precautions PPE use was assessed using each site's infection prevention policy, including if donning was completed before room entry or inside the room in an alcove area. Assessment of PPE use was also standardized across sites using a rule where PPE donning had to be completed in an alcove area if the HCP passed the alcove. HH adherence (hand rub/wash) was measured before room entry. Site policies were ranked on intensity (more PPE items required in more situations) and complexity (number of decisions required of HCP in order to don PPE appropriately). Results: Observations of PPE use and HH during room entry (>1100) were collected from 24 units (9 ICUs; 15 medicine/surgical units). Figure 1 shows the variation in application of precautions guideline. No facilities interpreted the guideline the same way and each differed in number of precautions types, required PPE and situation-dependent items, and organism-based approach. Sites are shown along a complexity vs. intensity continuum in Figure 2. Figure 3a and b shows PPE item-specific donning behavior. Glove donning ranged between 28-87% of room entries between facilities and gowns were donned for 22–82% of room entries. Entry HH behavior is included for comparison. The 4 facilities with highest, most similar gown and glove donning behavior had high intensity TBP policies; 3 of the 4 also had low complexity. Conclusion: This hypothesis generating study suggests PPE donning may occur more often among facilities with high intensity, low complexity policies. These results should be further investigated to assess if infection control policy intensity or fewer HCP decision points required to don PPE items is most associated with PPE donning behavior. Disclosures: All authors: No reported disclosures.